"Talkin' 'bout my generation" : conflicts of generation building and Europe's "1968" - Goltz, Anna von der 1978- Hrsg (Göttinger Studien zur Generationsforschung, 2011)
"The protests of '1968' have become a powerful symbol of generational belonging and central to the western world's collective memory. In many European countries, the '68ers' have been transformed into a mythical yardstick of what contitutes a generation. Yet few people thought of themselves in this way in the late 1960s: the idea of the '68er' only emerged from complex and often retrospective processes of generational building, both within countries and at an international level. Often labelled the first 'global generation', the term '68er' may have entered the vernacular across Europe, but what it entailed in different political and cultural contexts warrants examination. Were the '68ers' a pan-European phenomenon or did different generational entities emerge from national debates and discourses? The articles collected here examine the idea of a '68er' generation in West Germany, elsewhere in Western Europe, and in countries formerly behind the Iron Curtain. They address how activists - and those who observed them - made sense of those events at the time, how the idea of a generational experience was mobilized politically to powerful effect in the years that followed, and why the '68ers' have become the generation against which all others are measured in some countries, but not in others."--Publisher's description